2013
DOI: 10.1088/0004-637x/763/1/41
|View full text |Cite
|
Sign up to set email alerts
|

ON THE RELATIVE SIZES OF PLANETS WITHINKEPLERMULTIPLE-CANDIDATE SYSTEMS

Abstract: We present a study of the relative sizes of planets within the multiple-candidate systems discovered with the Kepler mission. We have compared the size of each planet to the size of every other planet within a given planetary system after correcting the sample for detection and geometric biases. We find that for planet pairs for which one or both objects are approximately Neptune-sized or larger, the larger planet is most often the planet with the longer period. No such size-location correlation is seen for pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 41 publications
16
115
1
Order By: Relevance
“…Although this is not the first time that planet size ordering in the Kepler multis has been shown (Ciardi et al 2013;Weiss et al 2017;Kipping 2018), here we have not only confirmed the observation of radius ordering but also extended it to mass.…”
supporting
confidence: 84%
“…Although this is not the first time that planet size ordering in the Kepler multis has been shown (Ciardi et al 2013;Weiss et al 2017;Kipping 2018), here we have not only confirmed the observation of radius ordering but also extended it to mass.…”
supporting
confidence: 84%
“…The architecture of this planetary system -containing a close-in giant planet and an outer Earth-sized planet with a period ratio larger than the 3:2 resonance -is certainly of interest for scenarios of planet formation and evolution . This system does not follow the trend reported by Ciardi et al (2013), that the larger planet has the longer period in the majority of Kepler systems of planet pairs with at least one Neptune-sized or larger planet.…”
Section: Characterization Of the Planetary System Kepler-101contrasting
confidence: 94%
“…Indeed, the system Kepler-101 does not follow the trend observed for ∼70% of Kepler planet pairs with at least one planet Neptune-sized or larger. In these systems, the larger planet typically has the longer period (Ciardi et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, the mass bin between 30 and 60 M ⊕ and the radius bin between 5 and 7 R ⊕ are among the most underpopulated, although objects with these characteristics should be relatively easy to find in high-precision photometric and spectroscopic datasets. Furthermore, data from the Kepler mission indicate that for multiple-planet architectures in which one object is approximately Neptune-sized or larger, the larger planet is most often the planet with the longer period (Ciardi et al 2013), and also that in general a lack of companion planets in hot-Jupiter systems is observed (e.g., Latham et al 2011;Steffen et al 2012).…”
Section: Introductionmentioning
confidence: 99%